Konten Isu Terorisme di Media Sosial dan Ketakutan Anggota Kepolisian - Ilham Prisgunanto; Teddy Rusmawan; Supardi Hamid (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2023)
Terrorism and radicalism as crimes are quite dangerous because they threaten security, property and life. The claim that terrorism and radicalism makes fear was tested in this research. The theoretical study of this research is the Social Information Processing theory and the Uses and Gratifications theory. The research method used is quantitative data processing with the independent variable internet network information content and the dependent variable is the fear and moral panic police officer (Indonesian Nasional Police). Survey research was conducted at the Surakarta Police (Polresta Surakarta) with 100 respondents as police officers. Research using simple linear regression model statistical data. The research findings show that there is no influence of internet network information content on issues of terrorism and radicalism on feelings of fear and panic among police officer. If there is a very small possibility, only 25.6%. The use of information technology by Police officer in the field is sufficient and sufficient to anticipate cases of terrorism and radicalism. The most powerful element seen by police officers regarding terrorism and radicalism is the narrative of the information presented which often does not make sense in the minds and thoughts of the police in the field.